2016
DOI: 10.5897/ajar2016.11316
|View full text |Cite
|
Sign up to set email alerts
|

Use of Bacillus spp. as growth promoter in carrot crop

Abstract: Growth promoting rhizobacteria may increase the yield of some crops. Several microbial products that stimulate plant growth have been marketed. Therefore, the objective of this study was to evaluate the effect of bacteria from Bacillus genera on the production of commercial carrot roots (Daucus carota L.) in field conditions. The following isolates: SF 264 (Bacillus spp.), SF 268 (Bacillus spp.) and commercial formulations based on SF 202 (Rizos®, B. subtilis), SF 266 (Quartz®, B. methylotrophicus) and SF 267 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Several other vegetables have been reported as responsive to microbial inoculants, including lettuce ( Lactuca sativa ) (Flores-Félix et al 2013; Mangmang et al 2014; Fasciglione et al 2015), carrot ( Daucus carota L.) (Flores-Félix et al 2013; Clemente et al 2016) and cucumber ( Cucumis sativus L.) (Mangmang et al 2015b). The increasing demands of the population on organic products may also stimulate the use of microbial inoculants for the production of vegetables.…”
Section: Main Inoculated Cropsmentioning
confidence: 99%
“…Several other vegetables have been reported as responsive to microbial inoculants, including lettuce ( Lactuca sativa ) (Flores-Félix et al 2013; Mangmang et al 2014; Fasciglione et al 2015), carrot ( Daucus carota L.) (Flores-Félix et al 2013; Clemente et al 2016) and cucumber ( Cucumis sativus L.) (Mangmang et al 2015b). The increasing demands of the population on organic products may also stimulate the use of microbial inoculants for the production of vegetables.…”
Section: Main Inoculated Cropsmentioning
confidence: 99%
“…These authors showed that, while the treatment with only N resulted in 28 g of roots, inoculation with the strain UCCBj-CE1 resulted in more than 60 g of roots. Clemente et al (2016) studied the response of carrots to Bacillus subtilis and B. methylotrophicus and observed increased fresh root mass in carrots. Without inoculation, the mean value was 5.9 kg m -2 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies on inoculation benefits in carrots are scarce and focus on a small number of measured parameters. Evaluations by Kozusny-Andreani et al (2014), Matsuoka et al (2016) and Clemente et al (2016) reported the benefits of Pseudomonas and Bacillus as increased root length, fresh mass and dry root mass.…”
mentioning
confidence: 99%
“…Due to their peculiar characteristics, these microorganisms have been employed in agriculture, increasing the resistance of plants to various environmental stresses such as drought, heavy metals, and nutritional scarcity of the soil (CLEMENTE et al, 2016). However, in the agricultural sector, Bacillus species are more widely studied and used as growth promoters and biological control agents against pests and diseases (CLEMENTE et al, 2016).…”
Section: Characterization Of Bacillus Spp Bacteriamentioning
confidence: 99%